A country drifting into political paralysis: reviewing Ali Riaz’s 'Pathways of Autocratization' - Hasan, Md. Mahmudul (The Daily Star, 2024)
For a Bangladeshi who loves and treasures their motherland, Ali Riaz's Pathways of Autocratization: The Tumultuous Journey of Bangladeshi Politics (Routledge, 2024) is a difficult read. It is so not because of any weakness in the presentation of the text or its arguments. Nor because of any contradiction in the content of the material investigated. What makes the book a heavy read is the fact that the writer leads the reader to the realisation that Bangladesh's regression into an authoritarian and autocratic regime, with associated atrocities, was foreseen and precipitated by actors inside and outside the country.